2005
DOI: 10.1128/ec.4.12.2029-2043.2005
|View full text |Cite
|
Sign up to set email alerts
|

Serial Analysis of Gene Expression Reveals Conserved Links between Protein Kinase A, Ribosome Biogenesis, and Phosphate Metabolism in Ustilago maydis

Abstract: The switch from budding to filamentous growth is a key aspect of invasive growth and virulence for the fungal phytopathogen Ustilago maydis. The cyclic AMP (cAMP) signaling pathway regulates dimorphism in U. maydis, as demonstrated by the phenotypes of mutants with defects in protein kinase A (PKA). Specifically, a mutant lacking the regulatory subunit of PKA encoded by the ubc1 gene displays a multiple-budded phenotype and fails to incite disease symptoms, although proliferation does occur in the plant host. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 79 publications
4
36
0
3
Order By: Relevance
“…The transport activity is not essential for the sensor function of Pho84, and targets of the PKA pathway are known to be regulated by the sensing activity of Pho84, thus indicating an influence on PKA activity (51,52,86,87). Our previous work also revealed that deletions in genes encoding components of PKA perturbed phosphate metabolism and polyphosphate formation in U maydis (35,36). Pho84 (and particularly Pho840) may also have a sensing function and influence PKA activity in C. neoformans.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The transport activity is not essential for the sensor function of Pho84, and targets of the PKA pathway are known to be regulated by the sensing activity of Pho84, thus indicating an influence on PKA activity (51,52,86,87). Our previous work also revealed that deletions in genes encoding components of PKA perturbed phosphate metabolism and polyphosphate formation in U maydis (35,36). Pho84 (and particularly Pho840) may also have a sensing function and influence PKA activity in C. neoformans.…”
Section: Discussionmentioning
confidence: 92%
“…In S. cerevisiae, Vtc4 was previously identified as a key component of the polyphosphate polymerase in the vacuolar transport chaperone complex that synthesizes polyphosphate at the vacuolar membrane (33,34). In this context, we previously showed that cAMP/PKA signaling influenced the expression of genes for phosphate uptake and storage in the fungal pathogen of maize, Ustilago maydis (35). One of the genes encoded Vtc4, and deletion of this gene reduced polyphosphate formation, influenced the transition between yeast and filamentous growth, and attenuated virulence (36).…”
mentioning
confidence: 99%
“…Others have been identified in a screen for genes regulated by cAMP-signalling (e.g. the aldo-keto reductase YakC, actin [20] and SEP3 [21]. However, additional proteins, not yet detected in other screens were also found to respond to b-locus induction.…”
Section: Identification Of Proteins Associated With Filamentous Growthmentioning
confidence: 99%
“…Two genes encoding catalytic subunits of protein kinase A (adr1 and uka1) have also been identified as part of cAMP signalling [38,39]. In the U. maydis adr1 mutant strain the septin SEP3 has been identified as being up-regulated in these filamentously growing cells [21]. The cAMP pathway thus suppresses expression of these genes.…”
Section: Interplay Of Signalling Pathways Involved In Filament Formationmentioning
confidence: 99%
“…Serial analysis of gene expression (SAGE) was previously performed to compare the transcriptomes of wild-type cells versus the PKA mutants ubc1 and adr1 (22). Mutation of the ubc1 gene, encoding the regulatory subunit of PKA, results in a multibudded phenotype.…”
mentioning
confidence: 99%